Depression symptom profiles and long-term response to cognitive behavioral therapy plus contingency management for smoking cessation. (1st August 2021) - González-Roz, Alba; Secades-Villa, Roberto; García-Fernández, Gloria; Martínez-Loredo, Víctor; Alonso-Pérez, Fernando
Highlights: Three classes of smokers based on baseline depressive symptoms were identified. Class 3 showed higher severity, increased appetite and feelings of punishment. Class 1 and 2 were more likely to be abstinent if CBT + CM was delivered. No sex x treatment effects were observed on smoking abstinence. Abstract: Background: Depression is heterogeneous in nature and using diagnostic categories limits insight into understanding psychopathology and its impact on treatment efficacy. This secondary analysis sought to: 1) identify distinct subpopulations of cigarette users with depression, and 2) examine their response to cognitive-behavioral treatment (CBT) + contingency management (CM) for smoking cessation at one year. Method: The sample comprised 238 (74 % females) adults who smoke receiving CBT only or CBT + CM. A latent class analysis was conducted on baseline depressive symptoms measured using the Beck Depression Inventory-II. Generalized estimating equations assessed the main and interactive effects of class, time, treatment, and sex on smoking abstinence. Results: Three distinct classes were identified: C1 ( n= 76/238), characterized by mild depression, loss of energy, pessimism, and criticism, C2 ( n= 100/238) presenting moderate severity and decreased appetite, and C3 ( n= 62/238) showing severe depression, increased appetite, and feelings of punishment. There was a significant cluster × treatment interaction, which indicated additive effects of CM over CBT alone for Class 1 and 2. Persons in Class 1 and 2 were 3.60 [95 % CI: 1.62, 7.97] and 2.65 [95 % CI: 1.19, 5.91] times more likely to be abstinent if CBT + CM was delivered rather than CBT only. No differential sex effects were observed on treatment response according to cluster. Conclusions: Profiling depression symptom subtypes of cigarette users may be more informative to improve CM treatment response than merely focusing on total scores.